Theoretical Approaches and Model Building in Scientific Research (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
This article examines the mechanisms of scientific research and the importance of their implementation processes. The article analyzes the necessary approaches, methods, and tools for conducting effective scientific research. Additionally, it highlights the role of model-building and theoretical approaches in scientific research and their contribution to creating innovative solutions.